The crystal facet effect of ZnAl2O4 in the CO2 hydrogenation to methanol - Hu, Yigong; Liu, Qiang; Wang, Zhiqun; Zhang, Xinle; Zhou, Xiangkun; Zhang, Guanghui; Guo, Xinwen (Frontiers in Chemical Engineering, 2026)
Zinc aluminate (ZnAl2O4) is one of the most widely used catalysts in the hydrogenation of carbon dioxide to methanol. During the CO2 hydrogenation reaction, ZnAl2O4 undergoes surface reconstruction to form ZnO, creating a ZnO/ZnAl2O4 active interface that promotes methanol production. However, the active crystal facets on which this surface reconstruction occurs, as well as the intrinsic and extrinsic factors influencing the reconstruction process, remain unclear, posing challenges to understanding the structure of the real active sites and the structure-activity relationship. In this work, ZnAl2O4 with three morphologies—granular, rod-like and plate-like—were synthesized, primarily exposing the (222), (311) and (440) crystal facets, respectively. The granular ZnAl2O4 exhibited superior methanol synthesis performance compared to the rod-like and plate-like morphologies. This enhancement is attributed to the reaction-induced formation of highly active ZnO predominantly exposing the (002) facet on the surface of granular ZnAl2O4. Furthermore, the intrinsic and extrinsic factors affecting the surface reconstruction process were investigated. Increasing the reaction temperature, the gas hourly space velocity (GHSV) and the H2/CO2 ratio were found to promote the surface reconstruction rate and enhance the steady-state space-time yield (STY) of oxygenates (Oxy). The granular ZnAl2O4, with its (222) facet featuring a spatial hexagonal arrangement of adjacent Zn atoms, exhibits stronger H2 activation capability, thereby promoting the surface reconstruction of active ZnO. These findings provide important guidance for the design and synthesis of highly efficient zinc-based oxide catalysts.